Ageratina adenophora (Spreng.) King & H. Rob. Standardized leaf extract as an antidiabetic agent for type 2 diabetes: An in vitro and in vivo evaluation - Chanu, Khaidem Devika; Sharma, Nanaocha; Kshetrimayum, Vimi; Chaudhary, Sushil Kumar; Ghosh, Suparna; Haldar, Pallab Kanti; Mukherjee, Pulok K. (Frontiers in Pharmacology, 2023)
Type-2 diabetes has become one of the major health concerns of the 21st century, marked by hyperglycemia or glycosuria and is associated with the development of several secondary health complications. The fact that chemically synthesized drugs lead to several inevitable side effects, new antidiabetic medications from plants has gained substantial attention. Thus, the current study aims to evaluate the antidiabetic capacity of Ageratina adenophora hydroalcoholic extract (AAHY) in streptozotocin-nicotinamide (STZ-NA)-induced diabetic wistar albino rats. The rats were segregated randomly into five groups with six rats each. Group I was normal control and the other four groups were (STZ-NA)-induced. Group II was designated diabetic control, Group III, IV and V received metformin (150 mg/kg b.w.), AAHY (200 and 400 mg/kg b.w.) for 28 days. Fasting blood glucose (FBG), serum biochemicals, liver and kidney antioxidant parameters, and pancreatic histopathology were observed after experimental design. The study concludes that AAHY has significant blood glucose lowering capacity on normoglycemic (87.01±0.54 to 57.21±0.31), diabetic (324±2.94 to 93±2.04) and oral glucose-loaded (117.75±3.35 to 92.75±2.09) wistar albino rats. The in-vitro studies show that AAHY has α- glucosidase and α-amylase inhibitory activities which can restore the altered blood glucose level, glycated hemoglobin, body weight, serum enzymes such as serum glutamic pyruvic transaminase, serum glutamic oxaloacetic transaminase, serum alkaline phosphatase, total protein, urea and creatinine levels close to normal range in the treated STZ-NA-induced diabetic rats. The evaluation of these serum biochemicals are crucial for monitoring diabetic condition. AAHY significantly enhanced tissue antioxidant parameters such as, superoxide dismutase, glutathione and lipid peroxidation, close to normal levels. The presence of a high quantity of chlorogenic (6.47 % w/w) and caffeic (3.28 % w/w) acids as some of the major phytoconstituents may contribute to the improvement of insulin resistance and oxidative stress. The study provides scientific support for the utilization of Ageratina adenophora to treat type-2 diabetes in STZ-NA-induced diabetic rat model. Although the preventive role of AAHY in treating wistar albino rat models against T2DM is undeniable, further elaborative research is required for efficacy and safety assessment in human.